C-alkylation of chiral tropane- and homotropane-derived enamines. - Hodgson, D; Charlton, A; Paton, R; Thompson, A (2013)
The synthesis and alkylation of chiral, nonracemic tropane- and homotropane-derived enamines is examined as an approach to enantioenriched α-alkylated aldehydes. The two bicyclic N auxiliaries, which differ by a single methylene group, give opposite senses of asymmetric induction on alkylation with EtI and provide modestly enantioenriched 2-ethylhexanal (following hydrolysis of the alkylated iminium). The observed stereoselectivity is supported by density functional studies of ethylation for both enamines.